Chitosan-based green sorbent material for cations removal from an aqueous environment. Issue 5 (October 2020) - Ali, Nisar; Khan, Adnan; Malik, Sumeet; Badshah, Syed; Bilal, Muhammad; Iqbal, Hafiz M.N.
Abstract: Herein, we report the development and characterization of a green sorbent material. For the said purpose, the chitosan's capacity of cation sorption was enhanced by incorporating thiocarabamate group, which ultimately increases active sites for attracting the cationic species. The process was carried out by utilizing acrylomorpholine, carbon disulfide and chitosan in a single stage process. The product (CH-ATC) acquired was well characterized with 13 C NMR (solid-form), FTIR spectroscopy, elemental investigation, thermogravimetic analysis and scanning electron microscopy. The novel product's ability of sorption was evaluated by applying it to lead and copper solution. The modified chitosan (CH-ATC) exhibited greater sorption capacity of lead (1.58 mmol g −1 ) over raw chitosan when applied to aqueous solution based on Langmuir sorption isotherm. The new material also showed reasonable sorption capacity for copper (1.25 mmol g −1 ). The experimentally obtained results associated well to Langmuir model than Temkin and Freundlich isotherms using linear regression method. Different linearization of Langmuir model showed different error functions and isothermal parameters. The nonlinear regression analysis showed lower values of error functions as compared to linear regression analysis. The chitosan with thiocarbamate chain is outstanding material for selected cations decontamination form aqueous solution.